Intrarectal Foreign Body Detected at CT Scanner Investigating an Abdominal Syndrome - Florina Popa; Madalina Grigoroiu; Monica Elia Georgescu (Case Reports in Surgery)
The field of general surgery offers many different pathologies, cases, and situations for which the general surgeons should be competent in diagnosis as well as treatment and management, including operative intervention. Most situations are complicated by delayed admission to the hospital due to the embarrassment of patient and inability to obtain satisfactory anamnesis. This article reviews the use of computed tomography as a problem-solving tool in the identification, localization, and presurgical planning for extracting the rectal foreign object.